Green Extraction of Bioactive Compounds from Peronema canescens Jack. Using Sodium Acetate/Glycerol-Based Natural Deep Eutectic Solvents as a Source of Natural Antioxidants - Tarigan, Indra Lasmana; Sinurat, Julius Alvin Novensius; Ramadhan, Iham Ifandi; Wijaya, Dhian Eka; Puspitasari, Ratih Dyah; Sowe, Momodou Salieu (Jurnal Kartika Kimia, 2025)
Peronema canescens Jack (commonly known as sungkai) is an endemic medicinal plant native to Sumatra and Kalimantan, known for its broad spectrum of pharmacological activities, including antioxidant, antibacterial, antidiabetic, antihyperuricemic, and anti-inflammatory effects. These properties are largely attributed to its high content of bioactive phenolic and flavonoid compounds. Conventional extraction techniques typically utilize organic solvents such as ethanol or methanol, which raise concerns regarding toxicity, cost, and environmental sustainability. This study explores a green extraction strategy employing Natural Deep Eutectic Solvents (NADES), formulated from sodium acetate and glycerol at varying molar ratios, to optimize the recovery of antioxidant compounds from sungkai leaves. The extraction process involved maceration for 2 × 24 hours. FTIR analysis identified key functional group absorptions (O–H, C–H, C=C), with distinct spectral shifts and intensity variations, indicating interactions between NADES components and bioactive molecules. Among the four tested formulations, NADES 4 (sodium acetate:glycerol, 1:3) yielded the highest total phenolic and flavonoid contents, and exhibited the strongest antioxidant activity, with an IC50 value of 32.30 ppm—classified as very strong and comparable to ascorbic acid. These results demonstrate that the compositional adjustment of NADES significantly influences solvent polarity and extraction efficiency, underscoring their promise as sustainable alternatives for the extraction of natural antioxidants.